Patient satisfaction level and its determinants after admission in public and private tertiary care hospitals in Bangladesh - Begum, Farhana; Said, Jamaliah; Hossain, Syed Zabid; Ali, Md. Ayub (Frontiers in Health Services, 2022)
Introduction: Patient satisfaction is an important indicator of quality of care provided by the health care facilities. The objective of the present study was to investigate the rate of satisfaction and its associated factors among the patients admitted to tertiary care hospitals of Bangladesh. Methods: This cross-sectional study was conducted in a public and two private tertiary care hospitals of Bangladesh during December 2019 including 923 consecutive patients admitted to medical and surgical departments. Face-to-face interview using a structured questionnaire was conducted to collect patient-level data. Logistic regression models were used to determine the factors associated with patients’ satisfaction. Results: Patients’ overall satisfaction level was 65% (51% in public and 75% in private hospitals) with a satisfaction rate of 63% in hospital staff courtesy, 56.5% in hospital environment, 67% in physician care, 63% in general patient satisfaction and 58% in patient’s family care. Private hospitals (aOR 3.64, 95% CI 2.20-6.03), conservative management (aOR 3.34, 95% CI 2.10-5.33), shorter hospital stay (aOR 1.58, 95% CI 1.05-2.37) and perceived improvement after treatment (aOR 1.67, 95% CI 1.01-2.76) were associated with patients’ satisfaction. In contrast, patients’ accommodation in floor (aOR 0.38, aOR 0.22-0.66) and high health care cost (aOR 0.97, 95% CI 0.95-0.99) was associated with patients’ dissatisfaction with the in-patient service they received in both public and private hospitals. Conclusion: Almost two-third of the patients were satisfied with the inpatient service they received, though, satisfaction rate was higher in private hospitals. Treatment modality, cost and outcome as well as hospital environment like accommodation were associated with their satisfaction level.